2022
DOI: 10.1111/nph.18284
|View full text |Cite
|
Sign up to set email alerts
|

Untying Gordian knots: unraveling reticulate polyploid plant evolution by genomic data using the large Ranunculus auricomus species complex

Abstract: Speciation via hybridization and polyploidization is a major evolutionary force in plant evolution but is still poorly understood for neopolyploid groups. Challenges are attributed to high heterozygosity, low genetic divergence, and missing information on progenitors, ploidy, and reproduction. We study the large Eurasian Ranunculus auricomus species complex and use a comprehensive workflow integrating reduced-representation sequencing (RRS) genomic data to unravel reticulate evolution, genome diversity and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 110 publications
5
52
0
Order By: Relevance
“…Apomictic polyploid complexes fit the definition of TCGs; they link intricate microevolutionary processes such as polyploidization, hybridization, and asexuality with macroevolutionary patterns [ 3 , 45 , 50 ]. Sexually diploid parents usually generate hundreds of hybrid, polyploid hybrid, and/or apomictic derivatives multiple times throughout time and space [ 38 , 51 , 52 , 53 , 54 ]. Particularly, the combination of polyploidy and hybridization (allopolyploidy) frequently shows higher degrees of (epi)genomic and transcriptomic changes than polyploidy alone (autopolyploidy) [ 3 , 7 , 55 , 56 , 57 ] and is thus more likely to create biotypes with novel phenotypic features [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apomictic polyploid complexes fit the definition of TCGs; they link intricate microevolutionary processes such as polyploidization, hybridization, and asexuality with macroevolutionary patterns [ 3 , 45 , 50 ]. Sexually diploid parents usually generate hundreds of hybrid, polyploid hybrid, and/or apomictic derivatives multiple times throughout time and space [ 38 , 51 , 52 , 53 , 54 ]. Particularly, the combination of polyploidy and hybridization (allopolyploidy) frequently shows higher degrees of (epi)genomic and transcriptomic changes than polyploidy alone (autopolyploidy) [ 3 , 7 , 55 , 56 , 57 ] and is thus more likely to create biotypes with novel phenotypic features [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that if genome size and/or chromosome counts might be useful tools for identifying polyploid complex L. suffruticosum s.l ., further studies were necessary to identify origin of the not easy disentangle polyploid complex. Another way but more expensive approach to phylogenetic studies involves (i) the use of organellar DNA (chloroplast or nuclear regions) as molecular markers as it was described for phylogenetic analysis of the genus Isoëtes (Pereira et al, 2019) or the diploid and autohexaploid cytotypes of Aster amellus (Mairal et al, 2018); or (ii) OMICS-data tools as RAD-Seq (restriction site-associated DNA sequencing) as described in the evolutionary processes of apomictic polyploid complexes on the model system Ranunculus (Karbstein et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This approach represents a compromise in orthology assessment, as distance-based methods are more scalable with taxa than tree-based methods (e.g., Yang and Smith 2014), but they do not explicitly assess homology in a phylogenetic context and may particularly have more difficulty distinguishing inparalogs (sensu Altenhoff et al 2019). Phasing has been of particular interest in the phylogenomics community, particularly in polyploids where they could mislead inference (Eriksson et al 2018;Nauheimer et al 2021;Karbstein et al 2022 but see Kates et al 2018).…”
Section: Methodsmentioning
confidence: 99%